Production and Shelf-Life of Low Sucrose Lime Juice Papaya Jam - Teangpook, Chowladda; Paosantong, Urai (Pakistan Journal of Nutrition, 2013)
Consumers are becoming more aware of the deleterious effects of a high-sucrose diet. This research developed low sucrose jam from ripe papaya meat and green lime juice. The shelf-life was studied: (A) in a refrigerator, (B) at room temperature with preservatives added and (C) at room temperature with steaming after filling. The developed jam was composed of 32% papaya, 8% lime juice, 0.55% low ester pectin, 0.5% konjac flour, 9% glucose syrup, 0.03% salt and 0.01% calcium lactate and consisted of 52.10% moisture, 45.61% total carbohydrate, 0% fat and 1.52% dietary fiber with only 7.71x105 J/100 g. It contained 36.46% sucrose, 46°B total soluble solids and had a pH of 3.22. The average sensory evaluation score was moderate preference and 79.31% of consumers liked it. The shelf-life of jam from A and B methods was more than six months but the C method was only five months.